HUBUNGAN KEMAMPUAN KOGNITIF DENGAN SIKAP SISWA PADA MATERI SISTEM PEREDARAN DARAH MANUSIA DI KELAS VIII SMP NEGERI 7 BINJAI - Rifkah Nafthali Tarigan; Tri Harsono; Yusriati Yusriati (Universitas Negeri Medan, 2017)
This study aims to determine the relationship between cognitive ability with the attitude of students of class VIII SMP N 7 Binjai Year Learning 2016/2017. The type of research used in this study is correlational research, the population in this study is all students of class VIII SMP Negeri 7 Binjai consisting of eight classes. The sample of this research is taken two classes that is class VIII1 and VIII2 which amounted to 70 people by random sampling, Data collection used was to use conitive ability test with 4 choiches of 25 items and questionnaires with 4 choiches of 40 items. The relationship between cognitive ability and student attitudes obtained an average of 69,65 and Standard Deviation (SD) of 13,45, while the average student attitude outcome was 82,52 and Deviation Standard (SD) of 6,84. The calculation results to find the regression equation Y over X obtained the equation Y = 73,31 + 0,12X, this shows the higher the cognitive abilities of students then the student’s attitude will also be better. By using the results of correlation coefficient test with product moment correlation, the value of rcalculate equal to 0,2598 which means there is a linier correlation between cognitive ability (X) with student attitude (Y). Based on the coefficient of determination test obtained contribution of 7% while the rest comes from other factors. In testing hypothesis with significance test (t test) obtained tarithmetic > ttable (2,434 > 1.974) at level significant α = 0,05. Thus the hypothesis (Ho) in this study is rejected and hypothesis (Ha) accepted that states there is a significant.Keyword: Cognitive Ability, Attitude, Human Circulatory System